2018
DOI: 10.5552/drind.2018.1754
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Extraction Technique on Composition of Volatile Constituents of Oleoresin from Pinus Brutia Ten.

Abstract: Utjecaj tehnike ekstrakcije na sastav hlapljivih sastojaka oleoresina iz drva Pinus brutia Ten.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…The findings regarding the main volatile compounds of brutian pine wood in this study are supported by Oz et al (2015) and Yasar et al (2018), who reported α-pinene, βpinene, β-caryophyllene, and Δ 3 -carene as the notable main components in the volatile compounds obtained from brutian pine.…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…The findings regarding the main volatile compounds of brutian pine wood in this study are supported by Oz et al (2015) and Yasar et al (2018), who reported α-pinene, βpinene, β-caryophyllene, and Δ 3 -carene as the notable main components in the volatile compounds obtained from brutian pine.…”
Section: Resultssupporting
confidence: 86%
“…In the brutian pine wood sample, α-pinene, β-pinene, β-caryophyllene, Δ 3 -carene, and α-humulene represented 73.34% of the total quantity of volatile compounds. These are known to be the main components of the turpentine oil of oleoresin obtained from brutian pine (Oz et al 2015;Yasar et al 2018). Oz et al (2015) reported the quantities of α-pinene, β-pinene, β-caryophyllene, Δ 3carene, and α-humulene to respectively represent 19.7%, 13.3%, 7.8%, 6.9%, and 3.3% (representing 51% of the turpentine oil of oleoresin from brutian pine).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Stable and efficient GC or GC–MS analysis methods has been established for the chemical composition analysis of pine resin, which can obtain the relative content of main components [ 8 , 9 ]. Recently, the methods based on the GC or GC–MS for verification and analysis of volatile essential oil composition (mainly including the α and β-pinene) were developed [ 10 , 11 ]. However, in addition to the expensive GC–MS spectrometry instrument, the GC–MS analysis method has high requirements for the experimental level and analytical ability of the operator.…”
Section: Introductionmentioning
confidence: 99%